The urban heat island effect in Dutch city centres - Leyre Echevarria Icaza; Frank van der Hoeven; Andy van den Dobbelsteen (A+BE: Architecture and the Built Environment, 2017)
In the Netherlands awareness regarding the Urban Heat Island (UHI) was raised relatively recently. Because of this recent understanding, there is a lack of consistent urban micro-meteorological measurements to allow a conventional UHI assessment of Dutch cities during heat waves. This paper argues that it is possible to retrieve relevant UHI information – including adaptation guidelines – from satellite imagery.